Design, Construction, and Rough-Terrain Locomotion Control of Novel Hexapod Walking Robot With Four Degrees of Freedom Per Leg - Petr Cizek; Martin Zoula; Jan Faigl (IEEE Access, 2021)
Multi-legged walking robots are suitable platforms for unstructured and rough terrains because of their immense locomotion capabilities. These are, however, redeemed by more sophisticated control and energy-demanding motion in comparison to wheeled robots. Particularly, electrically actuated multi-legged walking robots suffer from the adverse ratio between the robot body weight and payload capacity. Moreover, the locomotion speed and endurance ratio is far from what can be achieved with wheeled robots. In this paper, we focus on six-legged walking robots with statically-stable gait. Based on the analysis of existing solutions, we propose a novel construction of the affordable electrically actuated robot with substantial improvements in its motion capabilities, locomotion speed, reliability, and endurance. The proposed design is implemented in a Hexapod Ant Robot (HAntR) that is accompanied by the developed locomotion control approach to improve its rough terrains negotiation capabilities by the active distribution of the robot weight to the legs in the stance phase. Properties of the robot have been experimentally verified in extensive deployments, and based on the experimental benchmarking of the built prototype, HAntR is capable of locomotion for over an hour with the payload of 85% of its weight, and its maximum crawled distance per one second is 87% of its nominal length. HAntR represents significant improvements not only regarding the robots with identical actuators but also in comparison to other existing platforms. Therefore, we consider HAntR represents a step further towards a wide range of future applications and deployments of six-legged walking robots.